AB0767 Effect of Chondroitin Sulfate on Soluble Biomarkers of Osteoarthritis: How To Analyze and Interpret The Results from An Open-Label Trial in Unilateral Knee Osteoarthritis Patients. (15th July 2016) - Möller, I.; Gharbi, M.; Martinez, H.; Herrero, M.; Verges, J.; Henrotin, Y.
Abstract : Background: Changes in the level of biomarkers specific of osteoarthritis (OA) could help not only for the diagnosis but also for the monitoring of the disease progression and efficacy of a therapeutic intervention. Objectives: The aim of this study was to investigate the effects of chondroitin sulfate (CS) on the serum levels of biomarkers in patients with knee OA. Methods: Seventy two patients with unilateral symptomatic knee OA were involved in a post-authorization open-label study. Patients treated with CS (800 mg/day) were evaluated 5 times from D-30 to 6-month. The primary outcome was the % relative change in serum biomarkers (Coll2–1, Coll2–1NO2, Fib3–2). Secondary outcomes were the evaluation of pain (VAS) and function (Lequesne's Index). Responders and non-responders were classified according to OMERACT-OARSI recommendations. Finally, an original cut-off method was applied to categorize patients and interpret variations in serum levels of Coll2–1. Results: Patients from either ITT or PP populations showed no difference in the serum biomarkers levels at baseline. Most of the biomarkers levels decreased after 1 month of treatment but no significant differences were reported. However when considering responders and non-responders from the ITT population, a significant difference was found for Coll2–1 at 3 months (p=0.030) and 6 months (p=0.038) (ACA approach). A decrease in pain (VAS) and an improvement in function (LI) were recorded throughout the visits (p<0.01). The decrease in pain was significant at 1, 3 and 6 months in ITT and PP populations when compared to baseline. The improvement of function was shown to be significant after 6 months. Finally, an intra-batch cut-off of 22% was determined for Coll2–1 assay based on the variation of Coll2–1 between two blood collections in non-arthritic adult subjects. This value allowed the definition of metabolic responders as patients with variation of Coll2–1 by more than 22%.This means that a variation of 22% or less in the serum level of Coll2–1 consisted in a variation related to homeostasis. In contrast, a variation over this limit revealed either an increase or a decrease in cartilage catabolism. Considering these categories, CS decreased Coll2–1 serum levels between baseline and 1-month visit compared to the value of Coll2–1 before treatment (screening visit) which can be interpreted as a drastic reduction of the proportion of patients with an increase of Coll2–1 over 22% (reduction from 13% to 3). It also consisted in a more important proportion of patients with a decrease in Coll2–1. Conclusions: CS was effective modulating the metabolic status of KOA patients trough the reduction of Coll2–1 levels in responders and the disease's symptoms. Biomarkers are important tools for the monitoring of OA disease and of treatment. The main goal in biomarker research is to qualify them as surrogate endpoints in clinical trials. This study proposes a new approach for the analysis and the interpretation of the variation in biomarker levels and introduces the notion of metabolic responders. Disclosure of Interest: None declared